KONSEP KOMPETENSI KEPRIBADIAN GURU PAI - Khoerotun Ni'mah (Jurnal Pendidikan Agama Islam, 2014)
The teacher is one figure who became a guide and examples of conduct by the public in general and students in particular, because the teacher is a role model. Therefore, teachers must have the competencies that should maketh profile idol, one personal competence. Since the days previous to the present personality of a teacher get special attention in the world of education. When you look in history have also described the personality-emotion kepribadianyang owned by a teacher as found in the book of al-Muta’allim Ta’lim work Kitab az-Zarnuji and Adab al ‘Alim wa al-Muta’allim work KH. Hasyim Ashari. purpose of this study in order to conclude on the personality of the teacher according to the book of al-Muta’allim study groups and the Book of Adab al ‘Alim wa al-Muta’allim, so that the teacher can make the PAI personality guidelines that must be owned by a teacher by previous scholars to make it into the figure of the ideal teacher.